KONSEP PERGAULAN DALAM AL KAHFI - Junnifar, Ali; Sa'ad, Imam Muhammad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2022)
Humans are social creatures who need to get along with other people. The association should be able to complement each other's shortcomings, take lessons from each other, complement each other, and even increase one's level of faith. However, sometimes the association plunges us into disobedience if we are not careful in choosing our social partners. This research is written with the aim of giving awareness to humans about the dangers of choosing the wrong friend in a relationship by discussing the urgency of choosing social partners, etiquette in association, the characteristics of people who are worthy of being friends. After conducting a study of the concept of association in QS. Al-Kahf can be concluded that there are qualities in a person that we do not deserve to be friends, because if we make him friends, it will only plunge us into destruction. On the other hand, people who have qualities that we deserve to be friends with can increase the level of our faith, because they always invite goodness and remind each other not to do things that can lead to disobedience.